A flor da vida / Sementeira para a fenomenologia da pequena infância - Machado, Marina Marcondes (2007)
The thesis seeks to examine the adult-child relationship according to the precepts the philosopher Maurice Merleau-Ponty expounded in his Sorbonne lectures on child psychology and pedagogy. The thesis s author discusses in detail the concepts of otherness, corporeality, linguisticity, temporality, spaciality, mundaneity, and culpability in childhood and presents a register of the process of production of meaning in early childhood (from birth to six years of age). The author offers a drawn image which she calls The flower of life, in which the existentials appear as petals and mundaneity as the stem. The purpose is to show a conception of childhood in which the child s manner of being in the world is always holistic and understood as the child s coexistence with her body, with other people, with the time and space in which she lives, with her mother tongue, and with culpability. The author proposes a hermeneutics of childhood based on her work with children as theater teacher and psychotherapist. She concludes that the existencials ought to be carefully cultivated by adults, so that young children may acquire self-knowledge, knowledge of the other and of human culture. In this manner, under the guiding light of linguisticity, children from the earliest age on may acquire the capacity to express the meaning of their life experiences